Thermodynamic optimizations of the Nd-Sn and Sn-Tb systems. (March 2018) - Wang, S.L.; Su, X.H.; Li, S.S.; Fu, C.Y.; Guo, Y.H.; Huang, Y.X.; Xiang, D.H.; Wang, C.P.; Liu, X.J.
Abstract: The thermodynamic optimizations of the Nd-Sn and Sn-Tb binary systems were carried out by means of the Calculation of Phase Diagram (CALPHAD) method on the basis of the available experimental data including the thermodynamic properties and phase equilibria. The Gibbs free energies of the liquid, bcc, bct, dhcp and hcp phases were described by the substitutional solution model with the Redlich-Kister equation, while all of the intermetallic compounds (Nd5 Sn3, Nd5 Sn4, Nd11 Sn10, NdSn, Nd3 Sn5, NdSn2, Nd3 Sn7, Nd2 Sn5, NdSn3, Sn3 Tb, βSn7 Tb3, αSn7 Tb3, Sn2 Tb, Sn5 Tb4, SnTb4, Sn10 Tb11, Sn4 Tb5 and Sn3 Tb5 ) were described by the sublattice model. A set of self-consistent thermodynamic parameters of each phase in the Nd-Sn and Sn-Tb binary systems has been obtained, and the calculated results are in good agreement with the available experimental data.